The impact of resilience on the mental health of military personnel during the COVID-19 pandemic: coping styles and regulatory focus - Cao, Fei; Li, Juan; Xin, Wei; Yang, Zhibing; Wu, Di (Frontiers in Public Health, 2023)
Military personnel encountered multiple stressful events during the COVID-19 lockdown. Reducing non-combat attrition due to mental disorders is crucial for military morale and combat effectiveness. Grounded in stress theory and regulatory focus theory, this study investigates the influence of resilience on military personnel’s mental health; coping style and regulatory focus are considered potential mediators and moderators, respectively. We conducted a routine psychological assessment on 1,110 military personnel in China. The results indicate that: (1) resilience has a negative impact on the psychological symptoms of military groups; (2) mature and mixed coping styles in military personnel mediate the association between resilience and psychological symptoms; and (3) regulatory focus predominance has a negative moderating effect on mature coping styles’ effects on psychological symptoms. Furthermore, this study supports previous findings that resilience and mental health are interrelated; it demonstrates that military personnel can effectively reduce negative psychological symptoms by improving their resilience level and adopting mature coping styles under stressful situations. The current study presents interventional insights regarding coping styles and mental health from a self-regulatory perspective during the COVID-19 pandemic.